The radiological characteristics of childhood intussusception including unusual features and rare pathological lead points. Issue 6 (June 2021) - Khasawneh, Ruba; El-Heis, Mwaffaq; Al-Omari, Mamoon; Al-Qaralleh, Mohammed A.; Al-Manasra, Abdel rahman; Alqudah, Abdallah A.; Awad, Samah
Abstract: Purpose: To describe the radiological characteristics for childhood intussusceptions including unusual radiological features and rare pathological lead points (PLP). Material and methods: The medical records of all childhood intussusceptions between 1/1/2010 -1/10/2020 were retrospectively reviewed. 95 cases were identified in 82 patients. The demographic data, presenting symptoms, diagnostic and treatment methods, radiological features, and PLPs among the different types of intussusception were analyzed. Results: Ileocolic intussusception (ICI) represented 53.7% (51/95). The average age for ICI was 1.87 years. Males constituted 72.1% (31/43). 29.4% (15/51) were treated primarily surgically due to peritonitis. Small bowel intussusception (SBI) represented 40% (38/95) in which females constituted 51.5% (17/33). Ileo-ileal represented 63.2% (24/38). 81.8% (27/33) were transient. On ultrasound; There was a statistically significant difference in the size of the outer diameter of ICI compared to SBI (P-value 0.00012). Ileo-ileocolic and colo-colic intussusceptions constituted 3.2% (3/95); each and were more common in females. Vomiting was the most common symptom for intussusception and ultrasound was diagnostic in the majority of cases. PLPs were seen in 36.6% (30/82) of the patients of which the average age was 7 years. PLPs/risk factors were benign in 80% (24/30). A case of colo-colic intussusception was seen in a 16-year-old female due to clear cell sarcoma which was not reported before. 12.2% patients (10/82) had recurrent intussusception. Conclusion: Our study showed that ICI is the most commonly encountered type. SBIs are mostly transient. It is important to radiologically determine the type of intussusception and to identify PLPs or unusual radiological features to avoid unnecessary intervention and significant patient morbidity. Abstract : Childhood intussusception, Pathological lead point, Unusual feature, Ileocolic, Small bowel.